Clinical and prognostic utility of cardiovascular magnetic resonance imaging in myeloma patients with suspected cardiac amyloidosis. (25th May 2016) - Bhatti, Sabha; Watts, Evan; Syed, Fahd; Vallurupalli, Srikanth; Pandey, Tarun; Jambekar, Kedar; Mazur, Wojciech; Hakeem, Abdul
Abstract: Objectives: AL amyloidosis affects up to 30% of patients with multiple myeloma (MM), and cardiac involvement is associated with worse outcomes. Traditional screening modalities including EKG, echocardiography and biomarkers have limited value. The aim of this study was to evaluate the clinical and prognostic value of late gadolinium enhancement (LGE) by cardiovascular magnetic resonance (CMR) imaging in patients with plasma cell dyscrasias and suspected cardiac amyloidosis (CA). Methods: A total of 251 consecutive patients with plasma cell dyscrasias who underwent CMR were enrolled in this study. Primary endpoint was all cause mortality. Clinical, ECG, echocardiographic, biomarker and CMR predictors of mortality were analyzed. Results: Mean age of population was 63 ± 10 years, 36% females and 19% African Americans. During a median follow-up duration of 28 months (IQR 5–56), there were 97 deaths (39%). Patients who died were more likely to have diabetes (28% vs. 14%; P = 0.03), CAD (28% vs. 16%; P = 0.04) and CKD (33% vs. 21%; P = 0.04). With endomyocardial biopsy as the gold standard (42 (17%) patients), amyloid pattern on CMR (LGE+) had sensitivity and negative predictive values of 100%; specificity and positive predictive values of 80 and 81% with an AUC 0.9 for CA. History of CAD (HR 1.64, 95% CI 1.01–2.6; P = 0.04), brain natriuretic peptide (HR 1.0003 95% CI 1.0001–1.0006; P = 0.004) and LGE + (HR 1.72, 95% CI 1.05–2.8; P = 0.02) were independent predictors of mortality. LGE+ possessed incremental prognostic value over clinical, laboratory and echocardiographic variables for mortality prediction. Conclusions: CMR is a clinically useful tool for diagnosis and prognostication in myeloma patients with suspected CA.